Primer Extension Mutagenesis Powered by Selective Rolling Circle Amplification - Huovinen, Tuomas (Public Library of Science, 2012)
Primer extension mutagenesis is a popular tool to create libraries for in vitro evolution experiments. Here we describe a further improvement of the method described by T.A. Kunkel using uracil-containing single-stranded DNA as the template for the primer extension by additional uracil-DNA glycosylase treatment and rolling circle amplification (RCA) steps. It is shown that removal of uracil bases from the template leads to selective amplification of the nascently synthesized circular DNA strand carrying the desired mutations by phi29 DNA polymerase. Selective RCA (sRCA) of the DNA heteroduplex formed in Kunkel's mutagenesis increases the mutagenesis efficiency from 50% close to 100% and the number of transformants 300-fold without notable diversity bias. We also observed that both the mutated and the wild-type DNA were present in at least one third of the cells transformed directly with Kunkel's heteroduplex. In contrast, the cells transformed with sRCA product contained only mutated DNA. In sRCA, the complex cell-based selection for the mutant strand is replaced with the more controllable enzyme-based selection and less DNA is needed for library creation. Construction of a gene library of ten billion members is demonstrated with the described method with 240 nanograms of DNA as starting material.